The Analysis of Intention and Use of Financial Technology - Budi Rahardjo; Bintang Mukhammad Burhanudin Akbar; Ivo Novitaningtyas (Journal of Accounting and Strategic Finance, 2020)
The rapid development of technologies affects the financial technology sector, especially e-money in Indonesia. This research aims to analyze the determinant from intention and use behavior of financial technology (e-money) using UTAUT2 as the model. This research took place in Jabodetabek, with a total sample of 300 people as the respondents. The purposive sampling method is used as the sampling method in this study. The scale which is used in this study is the Likert scale with a range of 1-5. Data were analyzed using descriptive and Structural Equation Modeling (SEM). The results show that performance expectations, effort expectancy, social influence, facilitation conditions, and habits are factors that influence the intention and use of e-money. On the other hand, hedonic motivation and price value do not affect behavioral intention. It indicates that using financial technology is a must and not depend on user motivation or the price of the technology. These results provide implications about several factors as the determinant of e-money for stakeholders to develop the strategy for e-money based on the most influential factor that affects consumers as users. While developing e-money technology, the developer should take into account factors such as performance expectations, effort expectancy, social influence, facilitation conditions, and habits.